Learning models to improve higher-order thinking skills in mathematics: A systematic literature review - Kadarisma, Gida; Dewantara, Jagad Aditya (Program Studi Pendidikan Matematika Universitas Pasir Pengaraian, 2025)
Higher-Order Thinking Skills (HOTS) are essential abilities that students must possess in order to face complex problems and think critically. The role of learning models is crucial in developing students' HOTS, as they provide structured and meaningful learning experiences. Numerous learning models have been applied to facilitate and improve students’ higher-order thinking, particularly in mathematics. This study employed a Systematic Literature Review (SLR) approach, which involved collecting and analyzing previously published articles indexed by Google Scholar. The articles were gathered using the Publish or Perish software, with keywords such as